Postchikungunya Chronic Inflammatory Rheumatism - Keith A. Sacco; Razvan M. Chirila (Case Reports in Rheumatology)
A 65-year-old male resident of Guatemala presented with a 5-month history of distal symmetric arthritis and generalized fatigue. This was associated with night sweats, chills, and weight loss. Symptoms were refractory to oral prednisone and hydroxychloroquine.